Age related changes in striatal resting state functional connectivity in autism - Padmanabhan, Aarthi; Lynn, Andrew; Foran, William; Luna, Beatriz; O'Hearn, Kirsten (Frontiers in Human Neuroscience, 2013)
Characterizing the nature of developmental change is critical to understanding the mechanisms that are impaired in complex neurodevelopment disorders such as autism spectrum disorder (ASD) and, pragmatically, may allow us to pinpoint periods of plasticity when interventions are particularly useful. Although aberrant brain development has long been theorized as a characteristic feature of ASD, the neural substrates have been difficult to characterize, in part due to a lack of developmental data and to performance confounds. To address these issues, we examined the development of intrinsic functional connectivity with resting state fMRI from late childhood to early adulthood (8-36 years), using a seed based functional connectivity method with the striatum. Overall, we found that both groups show decreases in cortico-striatal circuits over age. However, when controlling for age, ASD participants showed increased connectivity with parietal cortex and decreased connectivity with prefrontal cortex relative to TD participants. In addition, ASD participants showed aberrant age-related changes in connectivity with anterior aspects of cerebellum, and posterior temporal regions (e.g. fusiform gyrus, inferior and superior temporal gyri). In sum, we found prominent differences in the development of striatal connectivity in ASD, most notably, atypical development of connectivity in striatal networks that may underlie cognitive and social reward processing. Our findings highlight the need to identify the biological mechanisms of perturbations in brain reorganization over development, which also may help clarify discrepant findings in the literature.